Canine hair follicular tumours: a retrospective study - Vala, Helena (2019)
Hair follicular tumours in dog comprise a large and heterogeneous group of neoplasms that display morphological features resembling one or several portions of the normal hair follicle which constitute a huge effort for its diagnosis. Histopathological evaluation is required to better characterize the different types of canine hair follicular tumours, in order to better understand its biological behaviour and to collaborate with the daily clinical practice. Thus, a retrospective, cross-sectional descriptive study was carried out with goal of analyse its frequency and characteristics, in order to contribute to a better understanding of this vast group of tumours. As main results the authors verified a higher incidence of follicular tumours in male dogs, being the most frequent types diagnosed trichoepithelioma, followed by, trichoblastoma, infundibular keratinizing acanthoma and pilomatricoma and the average age of dogs was 8.76 years. Also, malignant tumours represented 31.6% of all canine hair follicular tumours diagnosed (n= 114).